2015
DOI: 10.11648/j.sjph.20150302.29
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Hypertension among Adults. An Analysis of Survey Data on Chronic Non-Communicable Disease at Gilgel Gibe Field Research Center, South West Ethiopia

Abstract: Background: Population based survey study on hypertension risk factors among adults in Ethiopia are lacking. The objective of this study was to assess hypertension risk factors (socio-demographic and behavioural) among adults aged 15-64 years, at Gilgel gibe field research center, 2013. Methods: An analysis of population based cross-sectional survey data on chronic non-communicable diseases was carried on, between March and May 15, 2013 at the Field Center. Four thousand & fifty five individuals (hypertensive=… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(34 citation statements)
references
References 28 publications
2
29
3
Order By: Relevance
“…In five studies the prevalence of hypertension in male is higher than in female (17,18,19,21,22). Among all regions the highest prevalence is reported in the capital city of Ethiopia, Addis Ababa and the prevalence was 31.5% in male and 28.9% in female (21), the lowest prevalence is reported in Oromia region and the prevalence was 3.1% in male and 4.4% in female (16).…”
Section: Prevalence Of Hypertensionmentioning
confidence: 94%
See 3 more Smart Citations
“…In five studies the prevalence of hypertension in male is higher than in female (17,18,19,21,22). Among all regions the highest prevalence is reported in the capital city of Ethiopia, Addis Ababa and the prevalence was 31.5% in male and 28.9% in female (21), the lowest prevalence is reported in Oromia region and the prevalence was 3.1% in male and 4.4% in female (16).…”
Section: Prevalence Of Hypertensionmentioning
confidence: 94%
“…Age (15,19,20,22,23) and sex (16,18,19) are found to be associated with hypertension. Sleeping for less than five hours per a day (18), oral contraceptive pills (17), alcohol intake (17), waist circumference (15,21) physical inactivity (21-23), eating vegetable three or fewer days per week and salt use (22), obesity (20)(21)(22)(23), higher education (16,21) and vigorous recreational activities (16) were associated with hypertension.…”
Section: Risk Factors Of Hypertensionmentioning
confidence: 95%
See 2 more Smart Citations
“…Gender, educational level, alcohol use, and participated in vigorous recreational activity were found to be predictors of hypertension [14]. A hospital-based cross-sectional study found the percentage of those reporting a previous history of hypertension as 13.2%.…”
Section: Journal Of Community Medicine and Health Educationmentioning
confidence: 99%